Molded body

JP2025021159APending Publication Date: 2025-02-13SUMITOMO ELECTRIC INDUSTRIES LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023124915
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-13

AI Technical Summary

Benefits of technology

【0009】 [本開示の効果] 本開示によれば、耐摩耗性に優れ、互いに平行な一対の対向面の一方の面の深さ方向に電子線架橋体からなる架橋層が設けられていても、反り変形が抑制されたフッ素樹脂成形体を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021159000001_ABST
    Figure 2025021159000001_ABST
Patent Text Reader

Abstract

To provide a fluororesin molded body which is excellent in abrasion resistance, and suppresses warpage deformation, even if a crosslinked layer which is composed of an electron beam crosslinked body is provided in a depth direction on one surface of a pair of opposite surfaces parallel with each other.SOLUTION: A molded body contains a fluororesin as a main component and has a pair or a plurality of pairs of opposite surfaces parallel with each other, wherein a ratio of a constitutional unit having the same composition ratio of constitutional elements is 99 mol% or more in the total constitutional unit constituting the fluororesin, a crosslinked layer composed of an electron beam crosslinked body is provided in a depth direction on one surface in at least the pair of opposite surfaces, and a ratio of an average depth of the crosslinked layer to an average interval between the opposite surfaces provided with the crosslinked layer is 0.01% or more and 1.0% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a molded body. [Background technology]

[0002] Fluororesins such as polytetrafluoroethylene have excellent material properties such as chemical resistance, heat resistance, weather resistance, and insulating properties, and therefore molded articles using fluororesins are widely used.

[0003] It is known that crosslinking fluororesin by irradiating it with radiation such as electron beams or gamma rays improves its mechanical properties, creep resistance, radiation resistance, wear resistance, adhesion to other materials, and other properties. In the prior art, a sliding member made of fluororesin irradiated with ionizing radiation has been proposed. The prior art discloses a method in which a preform of a predetermined shape is manufactured from fluororesin, which is then baked, and then irradiated with ionizing radiation in the absence of oxygen while being heated to a temperature equal to or higher than the crystalline melting point of the fluororesin (see Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 9-278907 Summary of the Invention

[0005] A molded article according to one embodiment of the present disclosure is a molded article whose main component is a fluororesin and which has one or more pairs of opposing parallel surfaces, in which the proportion of structural units having the same composition ratio of constituent elements among all structural units constituting the fluororesin is 99 mol % or more, and in at least one pair of the opposing surfaces, a crosslinked layer made of an electron beam crosslinked product is provided in the depth direction of one of the surfaces, and the ratio of the average depth of the crosslinked layer to the average distance between the opposing surfaces on which the crosslinked layer is provided is 0.01% or more and 1.0% or less. [Brief description of the drawings]

[0006] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a molded article according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view for explaining a method for measuring the warpage rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] [Problem that this disclosure aims to solve] The present inventors have found that in a molded article containing a fluororesin as a main component, when one of a pair of parallel opposing surfaces is crosslinked by irradiating it with an electron beam, warping deformation is likely to occur.

[0008] An object of the present disclosure is to provide a fluororesin molded article that has excellent abrasion resistance and is suppressed in warpage deformation even when a crosslinked layer made of an electron beam crosslinked product is provided in the depth direction of one of a pair of parallel opposing surfaces.

[0009] [Effects of this disclosure] According to the present disclosure, it is possible to provide a fluororesin molded article that has excellent abrasion resistance and is suppressed in warpage deformation, even when a crosslinked layer made of an electron beam crosslinked product is provided in the depth direction on one of a pair of opposing parallel surfaces.

[0010] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be listed and described.

[0011] The molded body of the present disclosure is (1) A molded article whose main component is a fluororesin and which has one or more pairs of opposing parallel surfaces, wherein the proportion of structural units having the same composition ratio of constituent elements among all structural units constituting the fluororesin is 99 mol % or more, and at least one pair of the opposing surfaces has a crosslinked layer made of an electron beam crosslinked product provided in the depth direction of one of the surfaces, and the ratio of the average depth of the crosslinked layer to the average distance between the opposing surfaces on which the crosslinked layer is provided is 0.01% or more and 1.0% or less.

[0012] The molded article has excellent abrasion resistance by having the above-mentioned configuration, and warpage deformation is suppressed even if a crosslinked layer made of an electron beam crosslinked body is provided in the depth direction of one of a pair of parallel opposing surfaces of a molded article mainly composed of a fluororesin. The present inventors have found that when one of a pair of parallel opposing surfaces of the molded article is crosslinked by irradiating it with an electron beam, the mechanical properties, abrasion resistance, and other properties are improved, but the crosslinked layer shrinks and warpage deformation is likely to occur. The reason for this is unclear, but the following reason is presumed. When irradiated with an electron beam, the molecular chain of the fluororesin is cut, causing a decrease in the average molecular weight. It is also known that the molecular weight and specific gravity of the fluororesin are negatively correlated. That is, the specific gravity of the fluororesin increases as the molecular weight decreases. Even if the fluororesin molded article is irradiated with an electron beam, if crosslinking does not occur, the molecular chain is cut by the electron beam irradiation, causing a decrease in molecular weight and a rapid decrease in the strength of the irradiated layer at the same time, so that the fluororesin molded article does not shrink or warp. On the other hand, when a fluororesin molded product is crosslinked by electron beam irradiation, there is no particular decrease in strength, and in some cases the strength may increase depending on the irradiation conditions. In this case, it is considered that the specific gravity of the crosslinked layer irradiated with electron beams increases when it is integrated with the non-irradiated part below the crosslinked layer, that is, the volume of the integrated part decreases, causing shrinkage. In contrast, the molded article has an average depth of the crosslinked layer of 0.01% or more and 1.0% or less relative to the average distance, which improves abrasion resistance while reducing shrinkage due to crosslinking and suppressing warpage. The molded article is composed of the same composition, with the ratio of structural units having the same composition ratio of constituent elements being 99 mol % or more among all structural units constituting the fluororesin, and is first molded into a desired shape, and then a part of the outer surface is crosslinked by electron beam irradiation, so that the molded article can be applied to members of various shapes. Therefore, the molded article has excellent abrasion resistance, and it is believed that warpage deformation is suppressed even if a crosslinked layer made of an electron beam crosslinked product is provided in the depth direction of one of a pair of parallel opposing surfaces. In this disclosure, the term "main component" refers to the component with the highest content, for example, a component with a content of more than 90 mass%. The term "average interval" refers to the average value of the above interval measured at any ten points. The term "average depth of the crosslinked layer" refers to the average value of the depth of the crosslinked layer measured at any ten points.

[0013] (2) In the above (1), the average distance may be 1 mm or more and 50 mm or less. When the average distance between the opposing surfaces on which the crosslinked layers are provided is 1 mm or more and 50 mm or less, warpage can be further suppressed and processability can be improved.

[0014] (3) In the above (1) or (2), the molded body contains a conductive material and has a volume resistivity of 10 6 Ω or more 10 12 Fluorine resin has a high electrical resistance and tends to be charged with static electricity and attract dust. However, if the molded body contains a conductive material and has a volume resistivity of 10 6 Ω or more 10 12 By making the resistivity Ω or less, the effect of reducing electrical resistance can be improved, the generation of static electricity can be suppressed, and moldability can be improved. It is believed that the effect of reducing electrical resistance can be enhanced by irradiating with electron beams after dispersing the conductive material, and the effect of suppressing static electricity can be improved.

[0015] [Details of the embodiment of the present disclosure] A preferred embodiment of the present disclosure will now be described.

[0016] <Molded body> The molded article according to one embodiment of the present disclosure is a molded article that is mainly composed of a fluororesin and has one or more pairs of opposing surfaces that are parallel to each other. The shape of the molded article may be, for example, a plate, a rod, a cube, a rectangular parallelepiped, or a cylinder. In addition, for example, when the molded article has a plate shape, the cross-sectional shape may be a rectangle, a square, a parallelogram, or a trapezoid, and the corners of these cross-sectional shapes may be rounded.

[0017] The molded product has at least one pair of opposing surfaces, and a crosslinked layer made of an electron beam crosslinked product is provided in the depth direction of one of the surfaces. FIG. 1 is a schematic cross-sectional view showing a molded product 1 according to an embodiment of the present disclosure. The molded product 1 is plate-shaped. The molded product 1 has a pair of opposing surfaces, and a crosslinked layer 3 made of an electron beam crosslinked product is provided in the depth direction of one of the surfaces. In other words, the molded product 1 has a crosslinked layer 3 and a non-crosslinked layer 2 that serves as a main body.

[0018] The surface of the molded body 1 does not need to be flat, and may have a pattern such as a convex shape, a concave shape, or a continuous wave shape that alternately protrudes outward and inward in a cross-sectional view. The molded body 1 may have a through hole. In the case of a continuous wave shape, the cross-sectional shape of the adjacent convex and concave shapes is not particularly limited, and various shapes such as an isosceles triangle, a circular arc shape, an isosceles trapezoid, and a rectangle can be adopted. In this disclosure, "parallel" includes not only completely parallel but also substantially parallel, and it does not matter whether the surface of the molded body 1 has an uneven shape.

[0019] The lower limit of the average distance between the opposing surfaces on which the crosslinked layer is provided in the molded body 1 (between the first opposing surface on which the crosslinked layer is provided and the second opposing surface opposing the first opposing surface) may be 1 mm or 2 mm. On the other hand, the upper limit of the average distance may be 50 mm or 9 mm. When the average distance is 1 mm or more, the processability of the molded body 1 can be improved. When the average distance is 50 mm or less, the warpage deformation of the molded body 1 can be further suppressed.

[0020] The crosslinked layer 3 is made of an electron beam crosslinked product. The crosslinked layer 3 is formed by electron beam crosslinking on one of a pair of opposing surfaces of the molded product 1. The molded product 1 has the crosslinked layer 3, which provides abrasion resistance.

[0021] The upper limit of the ratio of the average depth of the crosslinked layer to the average interval is 1.0%, and may be 0.9%. If the ratio exceeds 1.0%, the shrinkage due to crosslinking of the molded body 1 cannot be sufficiently reduced, and the effect of suppressing warpage may not be obtained. On the other hand, the lower limit of the ratio of the average depth of the crosslinked layer to the average interval is 0.01%. If the ratio is less than 0.01%, the effect of suppressing warpage can be obtained, but for example, in the case of a molded body with an average interval of 1 mm, 0.01% of 1 mm is as thin as 0.1 μm, so if it is less than 0.01%, it may be difficult to obtain a stable crosslinking effect. When the ratio of the average depth of the crosslinked layer is 0.01% or more, the wear resistance of the molded body 1 can be improved. Note that the depth through which an electron beam penetrates is generally defined as the depth to which 80% of the total electron beam dose reaches, and therefore, in the present disclosure, this general indicator of "depth to which 80% of the dose reaches" is defined as the depth of the crosslinked layer.

[0022] The molded body 1 is mainly composed of a fluororesin. Since the molded body 1 contains a fluororesin as a main component, the molded body 1 has good chemical resistance, heat resistance, weather resistance, and non-stickiness. Examples of the fluororesin include tetrafluoroethylene-ethylene copolymer (ETFE), polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), polychlorotrifluoroethylene (PCTFE), and trifluorochloroethylene-ethylene copolymer (ECTFE). Among these, polytetrafluoroethylene is preferable as the fluororesin from the viewpoints of heat resistance, chemical resistance, and raw material costs.

[0023] The lower limit of the fluororesin content in the molded body 1 may be 91 mass%, 95 mass%, or 97 mass%. When the fluororesin content is within the above range, the chemical resistance, heat resistance, weather resistance, non-stickiness, etc. of the molded body can be further improved.

[0024] In the molded body 1, the proportion of structural units having the same composition ratio of constituent elements among all structural units constituting the fluororesin is 99 mol % or more. Since the proportion of structural units having the same composition ratio of constituent elements is 99 mol % or more, the molded body 1 can be applied to members of various shapes because a fluororesin of the same composition is first molded into a desired shape, and then a partial region of the outer surface is crosslinked by electron beam irradiation.

[0025] The molded body 1 contains a conductive material and has a volume resistivity of 10 6 Ω or more 10 12 Fluorine resin has a high electrical resistance and tends to be charged with static electricity and attract dust. However, when the molded body 1 contains a conductive material and has a volume resistance of 10 6 By having a volume resistivity of 10 Ω or more, the generation of static electricity can be suppressed. It is considered that the effect of reducing electrical resistance is enhanced by irradiating the conductive material with an electron beam after dispersing the conductive material, and the effect of suppressing static electricity can be improved. 12 By keeping the resistance below Ω, charging is suppressed, so that accumulation of electron beams and dielectric breakdown can be suppressed.

[0026] The conductive material is not particularly limited as long as it is a material having conductivity. Examples of the conductive material include carbonaceous materials, metals, and conductive ceramics. Examples of the carbonaceous material include graphite, non-graphitic carbon, and graphene-based carbon. Examples of the non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, and carbon black. Examples of the carbon black include furnace black, acetylene black, and ketjen black. Examples of the graphene-based carbon include graphene, carbon nanotubes (CNTs), and fullerenes.

[0027] The content of the conductive material is preferably set so that the volume resistivity falls within the above range. When the conductive material is carbon black, the content may be 3% by mass or more and 20% by mass or less. When the conductive material is carbon nanotubes, the content may be 0.3% by mass or more and less than 10% by mass.

[0028] The molded body 1 may contain, as other optional components, additives such as antifoaming agents, coloring pigments, antioxidants, UV absorbers, antistatic agents, surfactants, leveling agents, and rheology control agents.

[0029] [Method of manufacturing molded body] The method for producing the molded body includes a step of molding a resin composition containing a fluororesin as a main component into a desired shape, and a step of irradiating one of a pair of opposing surfaces of the molded body obtained in the molding step with an electron beam.

[0030] (Molding process) In the molding step, the resin composition containing the fluororesin as the main component is molded into a desired shape having one or more pairs of parallel opposing surfaces as described above. The resin composition is prepared by mixing the fluororesin and an arbitrary conductive material with components added as required using a kneader or the like. A known kneader can be used as the kneader. Alternatively, a resin composition that is commercially available as a material in which a conductive material has been mixed in advance can be used as the raw material.

[0031] The method for molding the molded body is not particularly limited, and may be any known method such as extrusion molding, injection molding, compression molding, followed by a cutting step, etc. In particular, when polytetrafluoroethylene is used as the main component, compression molding and cutting molding are preferred as the molding method in this step.

[0032] (Electron beam irradiation process) In the electron beam irradiating process, one of a pair of opposing surfaces of the molded body obtained in the molding process as described above is irradiated with an electron beam, thereby forming a crosslinked layer in the depth direction of one of the pair of opposing surfaces of the molded body.

[0033] Before being irradiated with electron beams, the temperature of the baked uncrosslinked molded body is adjusted to a temperature within the range of from 60° C. lower than the melting point of the fluororesin to 1° C. lower than the melting point. This temperature is called the irradiation temperature, and is a temperature for promoting crosslinking.

[0034] When the fluororesin is PTFE, the irradiation temperature may be 267°C to 326°C, 270°C to 325°C, 287°C to 324°C, or 302°C to 322°C. When the fluororesin is PTFE, the best results can be obtained within an irradiation temperature range of 305°C to 320°C. When the fluororesin is a mixture of PTFE and PFA, the irradiation temperature may be within the above range.

[0035] The dose of the electron beam in the step of irradiating the electron beam may be 50 kGy or more and 500 kGy or less, or 100 kGy or more and 300 kGy or less. If the dose of the electron beam is less than the lower limit, the wear resistance of the resulting molded body may not be sufficiently improved. On the other hand, if the dose of the electron beam is more than the upper limit, the cost-effectiveness of the electron beam irradiation may not be sufficiently obtained.

[0036] The electron beam irradiation condition in the step of irradiating with the electron beam may be an atmosphere having an oxygen concentration of 1,000 ppm or less.

[0037] In the manufacturing method of the molded article, the ratio of the average depth of the crosslinked layer to the average distance between the opposing surfaces on which the crosslinked layer is provided is set to 0.01% or more and 1.0% or less. This makes it possible to improve abrasion resistance while suppressing shrinkage due to crosslinking. Therefore, the manufacturing method of the molded article can produce a molded article that has excellent abrasion resistance and is suppressed in warpage deformation even if a crosslinked layer made of an electron beam crosslinked product is provided in the depth direction on one of a pair of parallel opposing surfaces.

[0038] The molded article has excellent abrasion resistance, and is suppressed from warping even if a crosslinked layer made of an electron beam crosslinked product is provided in the depth direction on one of a pair of parallel opposing surfaces.

[0039] [Other embodiments] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present disclosure is not limited to the configurations of the above-described embodiments, but is indicated by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims.

[0040] The molded article may have a plurality of pairs of opposing surfaces parallel to each other, and a crosslinked layer made of an electron beam crosslinked product may be provided in the depth direction of one of the pairs of opposing surfaces. In this case, in each of the pairs of opposing surfaces provided with the crosslinked layer, the ratio of the average depth of the crosslinked layer to the average distance between the opposing surfaces is 0.01% or more and 1.0% or less. EXAMPLES

[0041] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited to these examples.

[0042] [Test No.1~No.11] (1) Preparation of molded body Commercially available PTFE plates were used as the material for the molded bodies. Test samples of 40 mm square were cut out from 2 mm and 5 mm thick plates of "MTF-100" manufactured by Chukoh Chemical Industries, Ltd. For the conductive material-containing fluororesin, 5 mm plates of "4Y0" manufactured by Nippon Valqua Corporation, a PTFE material containing 3 mass% furnace carbon black, were cut into 40 mm squares in the same way to prepare test samples. (2) Electron beam irradiation Next, this molded body was irradiated with an electron beam at an acceleration voltage [keV] and exposure dose [kGy] shown in Table 1. The electron beam irradiation conditions were a nitrogen-substituted atmosphere and a surface temperature of the test sample of 320° C. In this way, molded bodies No. 1 to No. 11 were obtained.

[0043] [evaluation] (Warpage rate) 2, each of the molded articles 1 No. 1 to No. 11 was left for 1 hour in an environment with a temperature of 25°C and a humidity of 30% to 70%, and then placed flat so that the cross-linked layer 3 side was concave. The warpage rate (%) was calculated by the following formula when the amount of warpage (amount of lift) at the center in the longitudinal direction in a cross-sectional view of the molded article 1 was d mm and the length from the end to the center in the longitudinal direction of the molded article 1 was L mm. Warpage rate (%) = 100 x warpage at the center in the longitudinal direction d (mm) / length from the end to the center in the longitudinal direction L (mm)

[0044] (Limiting PV value by dry ring-on-disc wear test) For compacts No. 1 to No. 11, the limit PV value [MPa m / min] of the crosslinked layer surface was measured by ring-on-disk abrasion as follows. The measurement was performed under the condition that the load was constant at 10 MPa after adjusting the temperature at 23 ± 2 °C, and the speed was increased by one step every 3 minutes. Specifically, the material of the ring-shaped mating member was S45C (carbon steel for mechanical construction) with ring dimensions (outer diameter / inner diameter) of φ11.6 mm / φ7.4 mm was used. Then, each compact was rotated at a predetermined speed (rotation speed: V) with a load of 10 MPa (surface pressure: P) applied to the mating member under dry lubrication conditions, and the dynamic friction coefficient was measured by the reaction torque generated in the mating member. At this time, the speed started at 1 m / min in step (1), increased to 5 m / min in step (2), and increased to 10 m / min in step (3), and the speed was increased by 10 m / min for each step thereafter, and the limit PV value was measured. In this disclosure, the PV value immediately before the non-crosslinked layer of the molded article is exposed is defined as the limit PV value. For the above measurement, an AND Company "EFM-3-1010-S" test device was used. The abrasion resistance can be evaluated based on the limit PV value of the crosslinked layer surface.

[0045] (Volume resistivity) (1) Test No. 4 The volume resistivity of the obtained molded body of Test No. 4 was measured by the three-terminal method (double ring method) in accordance with JIS-K6911:1995. The specific test conditions are as follows. The results are shown in Table 1. Measurement conditions: Applied voltage DC10V, 60 seconds Number of measurements: n=1 Test environment: 23±2℃, 50±5%RH Measuring device: High resistivity meter Mitsubishi Chemical Analytech "Hirestar UP MCP-HT4500" URS probe electrode (electrode diameter: φ6mm) Mitsubishi Chemical Analytech "MCP-HTP14" (2) Tests No. 1 to No. 3 and No. 5 to No. 11 The volume resistivities of the obtained molded bodies of Test Nos. 1 to 3 and Test Nos. 5 to 11 were measured in accordance with JIS-K6911:1995. The specific test conditions were as follows. The results are shown in Table 1. Measurement conditions: Applied voltage DC 500V, 60 seconds Measurement temperature 23℃ Electrode dimensions: Main electrode diameter φ60mm, ring electrode inner diameter φ70mm, Back electrode φ80mm Electrode material: conductive rubber Number of measurements: n=1 Test environment: 23±2℃, 50±5%RH Measuring device: Super insulation meter Yokogawa Hewlett-Packard "4329A"

[0046] (Dielectric breakdown) After the electron beam irradiation, each test sample was visually evaluated for the presence or absence of dielectric breakdown.

[0047] The evaluation results of each of the above molded bodies are shown in Table 1.

[0048] [Table 1]

[0049] As shown in Table 1, in Test Nos. 1 to 4, in which the ratio of structural units having the same composition ratio of constituent elements among all structural units constituting the fluororesin is 99 mol % or more, in which a crosslinked layer made of an electron beam crosslinked product is provided in the depth direction of one of at least a pair of opposing surfaces, and in which the ratio of the average depth of the crosslinked layer to the average distance between the opposing surfaces provided with the crosslinked layer is 0.01% to 1.0%, the limit PV value was good and the warpage rate was low. Furthermore, in Test Nos. 1 to 3, in which the dose was 300 kGy, no dielectric breakdown occurred. In addition, in Test No. 4, even though the electron beam irradiation dose was as high as 1000 kGy, the volume resistivity was reduced by containing carbon black, and no dielectric breakdown occurred.

[0050] On the other hand, in Test No. 5 to Test No. 9, in which the ratio of the average depth of the crosslinked layer to the average interval exceeds 1.0%, the critical PV value was good, but the warpage rate was high. In Test No. 5 to Test No. 9, the dose was 300 kGy, so no dielectric breakdown occurred. Furthermore, in Test No. 11, in which a crosslinked layer made of an electron beam crosslinked body was not provided in the depth direction of one surface, no warpage deformation or dielectric breakdown was observed, but the critical PV value was very low. In addition, in Test No. 10, the electron beam irradiation dose was as high as 1000 kGy, and since the test sample did not contain carbon black, traces of insulation breakdown due to the discharge of electrons stored in the test sample after electron beam irradiation were observed.

[0051] The above results show that the molded body has excellent abrasion resistance and is suppressed from warping even when a crosslinked layer made of an electron beam crosslinked body is provided in the depth direction on one of a pair of parallel opposing surfaces. [Explanation of symbols]

[0052] 1 Molded body 2 Crosslinked layer 3 Non-crosslinked layer

Claims

1. A molded article containing a fluororesin as a main component and having one or more pairs of parallel opposing surfaces, Among all structural units constituting the fluororesin, the proportion of structural units having the same composition ratio of constituent elements is 99 mol % or more, a crosslinked layer made of an electron beam crosslinked product is provided in the depth direction of one of at least a pair of opposing surfaces, A molded article, in which the ratio of the average depth of the crosslinked layer to the average distance between the opposing surfaces on which the crosslinked layer is provided is 0.01% or more and 1.0% or less.

2. The molded article according to claim 1, wherein the average interval is 1 mm or more and 50 mm or less.

3. Contains a conductive material, Volume resistance is 10 6 Ω or more 10 12 The molded article according to claim 1 or 2, having a hardness of Ω or less.

Citation Information

Patent Citations

  • Sliding part material

    JP1997278907A